Effects of 12 weeks of strength training on anaerobic power in prepubescent male athletes - Hetzler, R. K.; DeRenne, C.; Buxton, B. P.; Ho, K. W.; Chai, D. X.; Seichi, G. (The Journal of Strength and Conditioning Research, 1997)
Two groups of 10 prepubescent and pubescent male baseball players trained three times per week for 12 weeks using a variety of general free-weight and machine exercises designed for both strength and power acquisition. One group was experienced in strength training while the other comprised novices. A comparable control group (N = 10) did not perform the training program but did participate in all other non-experimental activities. For the experienced, novice, and control groups respectively, the following gains were recorded: leg press -- 41%, 40%, and 14%; and bench press -- 23%, 18%, and 0%. Both training groups were significantly better than the control group. Similarly, the two training groups improved in vertical jump. However, the control group improved to a significantly greater degree in peak and mean anaerobic power and the 40-yard dash. The training regime improved the training activities but did not transfer to functional performance measures. One could argue that the training actually caused anaerobic power and 40-yd dash measures to decrease, particularly in the experienced strength-training group. The metabolic changes in training groups did not transfer changes in energy potential to dynamic cycling, supporting the principle of specificity. In particular, the high force/low velocity aspects of the training did not transfer to high velocity activities. Implication: Strength and power exercises in pubescent males improved training exercises but produced worse performances in functional strength and power activities than in a non-training comparable group. Performance benefits from such training for this class of athlete are unlikely.